"Magic" Number of Treadmill Sessions Needed to Achieve Meaningful Change in Gait Speed After Stroke: A Systematic Review. (18th September 2022) - Balinski, Mariah; Madhavan, Sangeetha
Abstract: The purpose of this systematic review was to determine the number of treadmill training sessions needed to make a meaningful change in gait speed for chronic stroke survivors. Relevant databases were searched up through February 2020. Articles were included if they fit the following criteria: stroke onset more than 5 mos, intention to treat with traditional treadmill training, and gait speed included as an outcome. Change in gait speed after intervention was used to classify treadmill groups as responders (at least 0.1 m/sec change) or nonresponders (less than 0.1 m/sec change). Seventeen articles met our criteria, resulting in a total of 19 intervention groups. Ten groups were classified as responders and completed a mean of 30.5 sessions within 6 wks, whereas nonresponders completed 20.4 sessions within 10 wks, indicating that at least 30 treadmill sessions (preferably in a period of 10 wks and at least 40 mins per session) is necessary to reach a meaningful change in gait speed. Although these trends were noted between the responder and nonresponder groups, no firm conclusions can be drawn regarding the "magic" number of sessions chronic stroke survivors should perform given the low correlation between number of sessions and change in gait speed.